Preparation of Fish Burger from Pangus Catfish (Pangasius sutchi) and Evaluation of Quality and Shelflife During Different Storage Conditions (Progressive Agriculture, 2013)
Improved fish burger was developed from pangus fish (Pangasius sutchi) by using different kinds of food additives (25% mashed potato, 2% NaCl, 2% oil, 2% spices such as onion, ginger, garlic, green chili, hot spices and 0.6% sugar). Proximate composition and sensory, chemical and microbiological changes of pangus fish burger were determined to evaluate the shelf life and storage stability kept at room (28ºC) and refrigeration (5ºC) temperature. It was observed that, the moisture, pH and protein contents in pangus burger were decreased than that of fish mince. On the other hand, lipid and ash contents were higher. Among the variable levels of mashed potato level, 25% mashed potato level showed the best sensory performance and was recommended for the commercial production. At room temperature, the sensory attributes deceased significantly (P